Key determinants of firm value: evidence from Serbian listed companies - Anja Šepa; Kristina Peštović; Nedeljko Tica; Dušan Saković (Anali Ekonomskog fakulteta u Subotici, 2024)
The valuation of a firm is a main issue that is scrutinized by all stakeholders and serves as an indicator of the worth of the core business. The goal of this study is to analyze, from both theoretical and empirical perspective, how key financial determinants influence firm value. In more detail, this study seeks to examine the relationships between firm value of listed companies in Belgrade Stock Exchange (BELEX) as a dependent variable, measured through Tobin’s Q, and independent variables that include leverage, size, liquidity, growth, asset structure and profitability. The aim of this paper is to provide an evaluation of the impact of firm-specific characteristics on the firm value of listed companies in Republic of Serbia, across several industries using panel dana analysis. The sample consists of 38 active companies that actively operated from 2019 to 2021, resulting in a total of 114 observations. The results of panel regression analysis show that on the one hand, liquidity and asset tangibility have positive and statistically significant influence on firm's value, while on the other hand, leverage and profitability have negative and statistically significant influence on the value of the firm. Company size and growth showed no statistically significant impact on Tobin’s Q.